A case of multiple myeloma initially presenting as hematemesis - Zhou, Hai-Bo (Turkish Journal of Gastroenterology, 2018)
Abstract A few cases of multiple myeloma with gastrointestinal bleeding have been reported, but hematemesis is rarely encountered as an initial symptom of multiple myeloma. Here we report a case of multiple myeloma with an initial symptom of hematemesis. Gastroscopy revealed ulceration in the angulus of the stomach. Colonoscopy revealed many ulcers in the ascending colon. A definite diagnosis of gastrointestinal amyloidosis was made using tissue biopsy. A definite diagnosis of multiple myeloma was made using bone marrow puncture. Hematemesis may be an initial symptom of multiple myeloma. A diagnosis of amyloidosis-induced hematemesis should be considered in patients with multiple myeloma. Cite this article as: Zhou HB. A case of multiple myeloma initially presenting as hematemesis. Turk J Gastroenterol 2018; 29: 104-7.